Pemikiran al-Irtifaqat Shah Waliullah Al-Dahlawi dalam membangun peradaban ekonomi umat Islam. - Muhammad Ulul Azmi; Syamsuri Syamsuri (JESI (Jurnal Ekonomi Syariah Indonesia), 2019)
One contribution in the concept of socio-economic or commonly referred to as al-Irtifaqat is Shah Waliullah al Dahlawi, a Delhi scholar born in the 18th century. According to him there are at least four concepts in the development of civil society, namely; (1) Beginning with the lives of primitive communities that are only oriented to meeting basic needs. (2) Humans rise to the level and start thinking about how to get a decent life. (3) The level of city life, and (4) the final stage is how humans reach the peak of civilization. Using qualitative methods and analyzed descriptively through a historical-normative-philosophical approach this article tries to describe Shah Waliullah al-Dahlawi's contribution in building the modern world civilization today, which in broadly outlines his ideas more on giving ideas about the concept of economic cooperation, taxation and responsibility state answer in the economy and so on.